Molecular characterization, expression and function analysis of Epinephelus coioides MKK4 response to SGIV and Vibrio alginolyticus infection. (June 2021) - Su, Yu-Ling; Jiang, Yu-Feng; Chen, He-Jia; Ye, Shi; Zhou, Wei-Hua; Liu, Hong-Ping; Dong, Jun-De; Wei, Jing-Guang; Qin, Qi-Wei; Sun, Hongyan
Abstract: Mitogen-activated protein kinase 4 (MKK4), a member of the MAP kinase family, play important roles in response to many environmental and cellular stresses in mammals. In this study, three MKK4 subtypes, EcMKK4-1, EcMKK4-2 and EcMKK4-3, were obtained from grouper Epinephelus coioides . The open reading frame (ORF) of EcMKK4s are obtained and the EcMKK4s proteins contain highly conserved domains: a S_TKc domain, a canonical diphosphorylation group and two conserved MKKK ATP binding motifs, Asp-Phe-Gly (DFG) and Ala-Pro-Glu (APE). EcMKK4s could be found both in the cytoplasmic and nuclear. The EcMKK4s mRNA were detected in all E. coioides tissues examined with the different expression levels, and the expression were up-regulated during SGIV (Singapore grouper iridescent virus) or Vibrio alginolyticus infection. EcMKK4 could significantly reduce the activation of AP-1 reporter gene. The results suggested that EcMKK4s might play important roles in pathogen-caused inflammation. Highlights: Mitogen-activated protein kinase 4 (MKK4) was characterized from Epinephelus coioides. E. coioides MKK4 mRNA was up-regulated during SGIV or Vibrio alginolyticus infection. E. coioides MKK4 can affect the activity of AP-1. E. coioides MKK4-3 can be involved in SGIV-induced early apoptosis.